2018
DOI: 10.1371/journal.pone.0207605
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular modelling and simulation studies of the Mycobacterium tuberculosis multidrug efflux pump protein Rv1258c

Abstract: Mycobacterial efflux pumps play a major role in the emergence of antimycobacterial drug resistance. Of particular interest is the proteinaceous multi-drug efflux pump protein Rv1258c that encodes a tetracycline/aminoglycoside resistance (TAP-2)-like efflux pump which is active in susceptible and drug resistant Mycobacterium tuberculosis. Rv1258c is implicated in drug resistance to numerous antimycobacterials including first line drugs rifampicin and isoniazid as well as fluoroquinolone and aminoglycoside antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Regarding aminoglycosides, no mutations were found at codon 1401 of the rrs gene with 43.9% of isolates resistant to STR in the BACTEC system. However, mutations have also been described in other genes, such as rpsL and gidB 7 , and other genes related to efflux pumps 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding aminoglycosides, no mutations were found at codon 1401 of the rrs gene with 43.9% of isolates resistant to STR in the BACTEC system. However, mutations have also been described in other genes, such as rpsL and gidB 7 , and other genes related to efflux pumps 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The template and the target sequence were aligned using the malign program in Modeller software [31]. Homology model of Rv0148 was constructed using Modeller and the quality of the model was further analysed using PROCHECK [32], ProSA-web [33] and verify 3D [34]. The model was also validated using root mean square deviation (RMSD).…”
Section: Template Selection and Homology Modellingmentioning
confidence: 99%
“…Docking was performed using NAD cofactor as the ligand with the predicted model of Rv0148 to understand its mode of interaction within the binding site. GOLD v5.2 (genetic optimization for ligand docking) is a widely used protein-ligand docking program [34]. GOLD uses a genetic algorithm methodology for protein-ligand docking that allows full ligand and partial protein flexibility.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…In the search for new treatments in cases of resistant TB, in which classical anti-TB drugs are not effective, the combinatory use of efflux pumps inhibitors (EPI), such as VP, has become the subject of some studies (Gupta et al, 2010a;Rodrigues et al, 2012;Cloete et al, 2018;Sharma et al, 2010). However, the experimental procedures for understanding EPI activity in M. tuberculosis are mostly limited to laboratory strains and few have been performed with clinical isolates (Machado et al, 2012), and divergence in results have been observed.…”
Section: Introductionmentioning
confidence: 99%